A comparative study of professional quality of life factors on mental health and psychosocial support (MHPSS) professionals working with earthquake victims and other trauma victims in Nepal. - Adhikari,Yuba Raj (2012)
ABSTRACT: Background: The professional quality of life (ProQOL), includes BO, STS and CS, of trauma care professionals, has been an understudied subject in Nepal. In post emergencies, the professionals face mental health challenges, and often the impacts may last longer (Ray et al., 2013); but the costs of care of Nepali trauma professionals were not considered in practice. This study complements to the gap. Aim: To examine the ProQOL situations and compare impacts of providing care to professionals in Nepal serving earthquake survivors and those serving other categories of trauma survivors. Methods: A non-experimental, comparative study model was used to examine the ProQOL characteristics of the groups of professionals using an online survey, which included ProQOL5 N. Multivariate analysis determined the differences in the ProQOL measures between the groups. : The overall ProQOL assessment revealed that Nepali professionals (N=112) are found to be in low of risks of BO (mean = 19.98), and a moderate level of risks for the STS (mean = 21.34), whereas, the overall CS was at a moderate level (mean = 41.19). Nevertheless, STS of professionals serving to non-earthquake survivors were found to be in higher risks. The MANOVA results outlined that CS, burnout and STS scores among the MHPSS professionals serving to both categories of trauma survivors were very similar without any significant differences (F (6, 216) = 0.575, p > .05). Conclusions: The ProQOL measures of Nepali MHPSS professionals serving to trauma survivors in post-earthquake are moderately affected by providing care; however, there were no significant differences in the impact on ProQOL measures among the professionals serving to various categories of trauma survivors. Need for further research to identify the factors contributing the positive outweigh of the negative effect of trauma care were outlined. Keywords: Cost of care, Post-earthquake, ProQOL, Nepali MHPSS professionals, Compassion Satisfaction Abstract word count: 299 Overall word count: 10955